2006
DOI: 10.1007/s11274-006-9312-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of bacteria from the rhizosphere of wheat

Abstract: In this study, we isolated bacteria from rhizosphere and endorhizophere of wheat crops of the central region of Argentina. The isolates were phenotypically characterized and the restriction patterns of 16S rDNA (ARDRA) using endonuclease AluI were analysed. Representative isolates were used to evaluate the effect of the inoculation on the growth of wheat under greenhouse conditions. The effects of plant growth-promoting bacteria on wheat plants were studied by evaluating shoot fresh and dry weights and root fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 34 publications
(32 reference statements)
5
45
0
1
Order By: Relevance
“…In our study, the two isolates showed activity of 3.90×10 -6 μmol α-keto butyrate/ mg protein/ h and 2.92×10 -6 μmol α-keto butyrate/mg protein/h by isolate UHI(II)7 and CHII(II)K7. Similar findings have been reported by other workers [47,48]. Plant growth by ACC deaminase producing Micrococcus sp.…”
Section: Figuresupporting
confidence: 93%
“…In our study, the two isolates showed activity of 3.90×10 -6 μmol α-keto butyrate/ mg protein/ h and 2.92×10 -6 μmol α-keto butyrate/mg protein/h by isolate UHI(II)7 and CHII(II)K7. Similar findings have been reported by other workers [47,48]. Plant growth by ACC deaminase producing Micrococcus sp.…”
Section: Figuresupporting
confidence: 93%
“…The final phylogenetic tree showed that the isolates were rather divers and from 40 isolates, 7 OTUs representing 31 isolates at the similarity of about 80% were obtained. Fingerprinting of 16S r-DNA has been used by many researchers to discriminate bacterial isolates genetically 7,12,45 . In such a similar practice, Loaces et al (2011), found 13 OTUs consisting of 55 isolates from 109 total isolates, whereas the rest showed unique restricted patterns indicating that the population density was quite variable .…”
Section: Discussionmentioning
confidence: 99%
“…The use of bio-fertilizers with a good management can decrease the leaching loss of nitrate and phosphate from the agricultural land and improve the ground water quality [190]. Also, the use of PGPR with low-fertilizer rate is also an environment friendly step and would be a viable supplementary strategy for further increasing crop yields [71,78,191].…”
Section: Pgpr Reduce Chemical Fertilizationmentioning
confidence: 99%